2017
DOI: 10.1007/s00405-017-4679-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported pain-related outcome measures after tonsil surgery: an analysis of 32,225 children from the National Tonsil Surgery Register in Sweden 2009–2016

Abstract: The objective of this study was to describe factors affecting pain after pediatric tonsil surgery, using patient reported pain-related outcome measures (pain-PROMs) from the National Tonsil Surgery Register in Sweden. In total, 32,225 tonsil surgeries on children (1 to <18 years) during 2009–2016 were included; 13,904 tonsillectomies with or without adenoidectomy (TE ± A), and 18,321 tonsillotomies with or without adenoidectomy (TT ± A). Adjustments were made for variables included in the register to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Older children and those with recurrent tonsillitis may experience greater pain than young children with obstruction. [24][25][26][27][28] In this study, 22 children were older than 6 years (14 and 8 in the LTD and ES groups, respectively) and 13 children had recurrent tonsillitis (6 and 7 in the LTD and ES groups, respectively). Thus, it is unlikely that older age or diagnosis explains the greater pain medication use in the ES group.…”
Section: Discussionmentioning
confidence: 76%
“…Older children and those with recurrent tonsillitis may experience greater pain than young children with obstruction. [24][25][26][27][28] In this study, 22 children were older than 6 years (14 and 8 in the LTD and ES groups, respectively) and 13 children had recurrent tonsillitis (6 and 7 in the LTD and ES groups, respectively). Thus, it is unlikely that older age or diagnosis explains the greater pain medication use in the ES group.…”
Section: Discussionmentioning
confidence: 76%
“…This corresponds to previous literature which has shown that older children may experience more pain, as well as increased analgesic use and delayed return to day-to-day functioning than younger children following T&A surgery. [44,45] Since UE dyads were of higher age, on average, 336 it is worthwhile to provide specific instructions to parents of older children on potentially higher 337 pain rates. Ultimately, is of most critical importance to provide concrete directions to all parents on identifying and treating child postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that families who had the organizational strength to complete and return the diary also had better adherence to analgesic treatment compared to families who did not return the diary. However, some results (duration of analgesics) were similar to randomized controlled trials (RCTs) and register studies [10,17]. The present study did not include highly sensitive measures to identify the impact of different analgesic regimens (e.g., clonidine), which is why there is still no consensus as to the most effective postoperative pain control regimen after tonsil surgery.…”
Section: Discussionmentioning
confidence: 72%
“…2). There was no significant difference in the percentage of child-parent disagreement between the older and younger children (ages 12-17 vs. [4][5][6][7][8][9][10][11]. A weighted kappa analysis of all child-parent pain assessments during days 1-3 resulted in a kappa coefficient of 0.57.…”
Section: Severity and Duration Of Postoperative Painmentioning
confidence: 85%
See 1 more Smart Citation